2018
DOI: 10.1016/j.oret.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

OCT Angiography Changes in the 3 Parafoveal Retinal Plexuses in Response to Hyperoxia

Abstract: Purpose Use projection-resolved OCT angiography to investigate the autoregulatory response in the 3 parafoveal retinal plexuses under hyperoxia. Design Prospective cohort study. Participants Nine eyes from 9 healthy participants. Methods One eye from each participant was scanned using a commercial spectral-domain OCT system. Two repeated macular scans (3 × 3 mm2) were acquired at baseline and during oxygen breathing. The split-spectrum amplitude-decorrelation algorithm was used to detect blood flow. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 54 publications
7
42
2
Order By: Relevance
“…43 The plexuses may respond differently to systemic condition alteration, such as changes in BP and oxygenation, or to retinal functional hyperemia evoked by a flickering light stimulus. [44][45][46] In our study, antihypertensive drugs and eGFR were associated with vessel density in SVP, but not in DVP. On the contrary, smoking was associated with vessel density in DVP, but not in SVP.…”
Section: Ckd Stage N (%)contrasting
confidence: 41%
See 1 more Smart Citation
“…43 The plexuses may respond differently to systemic condition alteration, such as changes in BP and oxygenation, or to retinal functional hyperemia evoked by a flickering light stimulus. [44][45][46] In our study, antihypertensive drugs and eGFR were associated with vessel density in SVP, but not in DVP. On the contrary, smoking was associated with vessel density in DVP, but not in SVP.…”
Section: Ckd Stage N (%)contrasting
confidence: 41%
“…Each capillary plexus has different anatomical structures and may have its own autoregulation . The plexuses may respond differently to systemic condition alteration, such as changes in BP and oxygenation, or to retinal functional hyperemia evoked by a flickering light stimulus . In our study, anti‐hypertensive drugs and eGFR were associated with vessel density in SVP, but not in DVP.…”
Section: Discussionmentioning
confidence: 64%
“…57,59,60 The findings of the recent hyperoxia experiments suggest that deeper retinal plexuses, especially the DCP, contribute to the nourishment of outer retinal layers, along with choroidal circulation. 39 Thus, we expected that outer retinal degeneration will cause a decrease in metabolic demand, and consequently secondary vascular remodeling and attenuation. This hypothesis was further supported by the strong correlation between perifoveal changes in the VD in the DCP and ICP, and the perifoveal outer retinal thickness in RP patients with no history of CME.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently developed projection-resolved OCTA (PR-OCTA) algorithm 33,34 to significantly suppress projection artifacts, allowing for proper segmentation of retinal circulation, and in turn more reliable visualization and quantification of microvasculature. [35][36][37][38][39][40][41][42][43][44][45] In this study, we aim to characterize the alterations in perfusion in all three retinal plexuses, as well as the relationship between vascular and structural changes in RP patients.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Changes in each of the three distinct capillary plexuses have been described for specific conditions, such as diabetic retinopathy (DR), hyperoxia, and dark adaptation, and it has been demonstrated that each vascular layer undergoes independent changes. [23][24][25][26] But, these studies lack definitive evidence for segmentation.…”
Section: Introductionmentioning
confidence: 99%